P489 Clinical experience with ustekinumab in selected Crohn's disease patients. (16th January 2018) - Saman, S; Klag, T; Wendler, J; Goetz, M; Malek, N P; Wehkamp, J
Abstract: Background: Ustekinumab – an interleukin-12/23 antibody has been shown to be efficient in moderately to active Crohns disease with a more favourable outcome in anti TNF naïve patients. After approval of the drug we first treated patients who were both either non-responders to anti TNF and or some also refractory to a4b7-integrin inhibitor Vedolizumab. Of note, a significant proportion of our IBD centre patients would not have been qualified for the known Phases II and III study inclusion criteria for different reasons (Feagan et al; Sandborn et al). Thus, in a retrospective, observational study, we aimed to assess the clinical outcome independent of study criteria in a highly selected patient group. Methods: A group of 38 adults with moderately to severely active Crohns disease who had either lost response, or were intolerant to either conventional therapy (steroids, azathioprine) ( n = 32), or Vedolizumab ( n = 7) and or TNF-α antagonists ( n = 37) were treated with Ustekinumab. IV (6 mg/kg) at Week 0 was followed by s.c. Ustekinumab (90 mg) at Week 8. Depending on the clinical response patients were either stopped or received maintenance therapy every 8 or 12 weeks. Clinical response was defined by either CDAI decline of more than 100 points, decline of stool frequency or clinical improvement defined by patients well-being and physicians observations. Haemoglobin (HB) and CRP levels were analysed as potential biomarkers. Patients were also monitored for side effects. Results: About a third of our patients were outside the approval study inclusion criteria. 84, 2% of the patients had been treated with Azathioprine and 47, 4% had been treated with two anti-TNF drugs among other immunosuppressives before being treated with Ustekinumab. Overall, 63, 2% ( n = 24/38) of the patients showed a clinical response to the treatment with Ustekinumab while about half of this group achieved remission. 11 (28, 9%) did not respond to the treatment. Response correlated with improvement of HBD ( p = 0.0144) after second application of Ustekinumab and also with a drop in stool frequency ( p = 0.003). The CDAI score improved after the first application of Ustekinumab ( p ≤ 0.0001). Of note, there was no correlation between disease activity and the CRP ( p = 0.2188). 37 of 38 patients tolerated the drug well and we observed no related infections. Overall, with the limitation of small groups, we did not see significant differences depending on published inclusion criteria or previous therapy. Conclusions: Ustekinumab is an effective, safe and well tolerated drug. CRP did not serve as a valid marker for predicting response. Current and future effort should aim to preselect patient and better predict outcome based on personalised approaches.